Caffeic acid phenethyl ester synergistically enhances docetaxel and paclitaxel cytotoxicity in prostate cancer cells. Issue 8 (11th July 2013) - Tolba, Mai F.; Esmat, Ahmed; Al‐Abd, Ahmed M.; Azab, Samar S.; Khalifa, Amani E.; Mosli, Hisham A.; Abdel‐Rahman, Sherif Z.; Abdel‐Naim, Ashraf B.
Abstract Evidence is growing for the beneficial role of selective estrogen receptor modulators (SERM) in prostate diseases. Caffeic acid phenethyl ester (CAPE) is a promising component of propolis that possesses SERM activity. This study aimed at investigating the modulatory impact of CAPE on docetaxel (DOC) and paclitaxel (PTX) cytotoxicity in prostate cancer cells and exploring the possible underlying mechanisms for this chemomodulation. CAPE significantly increased DOC and PTX potency in PC‐3, DU‐145 and LNCaP prostate cancer cells. Combination index calculations showed synergistic interaction of CAPE/DOC and CAPE/PTX cotreatments in all the tested cell lines. Subsequent mechanistic studies in PC‐3 cells indicated that cyclin D1 and c‐myc were significantly reduced in the combined treatment groups with concurrent increase in p27kip. DNA‐ploidy analysis indicated a significant increase in the percentage of cells in pre‐G1 in CAPE/DOC and CAPE/PTX cotreatments. Decreased Bcl‐2/Bax ratio together with increased caspase‐3 activity and protein abundance were observed in the same groups. Estrogen receptor‐β (ER‐β) and its downstream tumor suppressor forkhead box O1 levels were significantly elevated in CAPE and combination groups compared to DOC or PTX‐alone. ER‐α and insulin‐like growth factor‐1 receptor protein abundance were reduced in the same groups. CAPE significantly reduced AKT, ERK and ER‐α (Ser‐167) phosphorylation in PC‐3 cells. CAPE‐induced inhibition of AKT phosphorylation was more prominent (1.7‐folds higher) in cells expressing ER‐α such as PC‐3 compared to LNCaP. In conclusion, CAPE enhances the antiproliferative and cytotoxic effects of DOC and PTX in prostate cancer cells. This can be, at least partly, attributed to CAPE augmentation of DOC and PTX proapoptotic effects in addition to CAPE‐induced alterations in ER‐α and ER‐β abundance. © 2013 IUBMB Life, 65(8):716–729, 2013